International Conference on Development and Socio Spatial Inequalities 2015 – Bridging Socio-Spatial Inequalities through Inclusive Development - PPIK, Pusat Pengajian Ilmu Kemanusiaan (School of Humanities, USM, 2015)
Despite significant advance in development across the globe, progress has been uneven. It has been very rapid in East Asia Latin America and some parts of Middle East, but slow in South Asia and sub-Sahara Africa. Wealth per capita is often used to measure development and categorize countries into low, lower middle, upper middle and upper income countries. Thus, variations in development and subsequent wealth generation have led to widening of gaps between rich and poor countries. This phenomenon has exacerbated inequality among regions and nations. Socio-spatial inequality can be described as unequal distribution and concentration of resources and services such as medical, welfare and education depending on area or location. It can be caused by culture, religion, race, or remoteness of the areas. This situation can be identified by spatial analysis, where spatial dimension is used to describe patterns of inequality. Furthermore, spatial variation may be compared between different geographical areas in relation to social, culture and environment. This phenomenon may become persistent and self-perpetuating, causing serious economic and social problems. It is pertinent, therefore, to detect issues of inequalities between different areas, or between ethnics groups and find strategies and policies to reduce these inequalities. Thus, making distribution of resources and services more even.